Comparison between the Effect of Teaching through StudentBased Group Discussion and Lecture on Learning in Medical Students - Manoochehr Mahram; Behrooz Mahram; Seyyed Nouroddin Mousavinasab (Kerman University of Medical Sciences, 2009)
Background & Objective : It has been years that the traditional method of lecture is used for teaching and both teachers and students are unsatisfied with this methods tediousness and low efficacy According to low experience in teaching theoretical clinical courses via studentbased group discussion in small groups this study was performed to compare learning resulted from the aforementioned method and lecture Methods In this semiexperimental study lecture and group discussion in small groups (6 to 8 members) were tested in theoretical course of pediatrics in four series of students in Zanjan School of Medicine Some topics were taught using lecture while others were taught using studentbased group discussion At the end of all classes quizzes were given to the students the results from these quizzes and final exams were compared in both teaching methods Results The mean percentage of correct answers in quizzes in methods of group discussion and lecture were 84% and 45% respectively which was significantly different (P = 00001) The mean percentage of correct answers to the questions in final exams was 67% and 65% for group discussion and lecture accordingly while there was no significant difference(P=019) Conclusion : Regarding the results of this study and similar researches learning via group discussion seems to be more profound and effective but this profundity was not present in the final exam which may be due to the defects in designing questions and emphasizing on students memorized content